The indigo spell : a bloodlines novel - Mead, Richelle (Mead, Richelle. Bloodlines novel, 2013)
As former Alchemist Marcus Finch pushes Alchemist Sydney Sage to rebel against the people who raised her, Sydney finds that breaking free is harder than she thought. There is an old and mysterious magic rooted deeply within her. And as she searches for an evil magic user targeting powerful young witches, she realizes that her only hope is to embrace her magical blood--or else she might be next.